África : reflexión geográfica sobre su población y compartimentación territorial - Torres Luna, María del Pilar de (Espacio Tiempo y Forma. Serie VI, Geografía, 1996)
The present article, as its title says, wants tries to be a reflection in geographical key of most outstanding aspects on the current Áfrican population. The thread rurls from ethnographic study and the peoples settied in África, as far as their social and demographic behaviour since the decolonization startes massively in 1960s. In the last part some essays on geographical landscape compartrnentalization of nowadays áfrica are taken into account commented.